Determinants of Financial Literacy among German Students: An Empirical Analysis - Katharina Riebe (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
Financial literacy is very important for social participation. This paper presents an empirical evaluation of the determinants of financial literacy among students at a German university. An additional goal is the identification of gender differences in respect to financial literacy. The evaluation is based on the definition and surveys of financial literacy developed by the OECD, (A. Lusardi & Mitchell, 2014) and (Chen & Volpe, 1998) and the analysis of the "Big Three" questions. The results suggest a rather low level of financial literacy among female students. Additional factors such as a very good mathematics grade and logical thinking have a significantly positive impact on financial literacy. Students in economics are more likely to answer the "Big Three" questions correctly. This finding supports the hypothesis that education in economics helps to acquire knowledge of financial instruments and financial application. – – Finanzkompetenzen haben für die gesellschaftliche Teilhabe eine hohe Bedeutung. Dieser Beitrag führt eine empirische Evaluation der Determinanten der Finanzkompetenz von Studierenden an einer deutschen Hochschule durch. Ein weiteres Ziel ist auch die Identifizierung der geschlechtsspezifischen Unterschiede bei der Finanzkompetenz. Die Evaluierung basiert auf der Definition und den Erhebungen zur Finanzkompetenz, die von der OECD entwickelt wurden, (A. Lusardi & Mitchell, 2014) und (Chen & Volpe, 1998) sowie auf der Analyse der "Big Three"-Fragen. Die Ergebnisse deuten auf ein eher geringeres Niveau der Finanzkompetenz unter Studentinnen hin. Weitere Faktoren wie eine gute Mathematiknote und logisches Denken haben signifikant positive Auswirkungen auf die Finanzkompetenz. Studierende der Wirtschaftswissenschaften beantworten die "Big Three"-Fragen mit höherer Wahrscheinlichkeit richtig. Dieses Ergebnis unterstützt die Hypothese, dass die wirtschaftswissenschaftliche Bildung dazu beiträgt, Kenntnisse über Finanzinstrumente und deren Anwendung zu erwerben.
Keywords: A22; D14; D80; D91; G53; I21; I22; I23; I24; 330; financial skills; Gender; higher education; determinants of financial literacy